Anti gonadotropic by use of chorionic gonadotropin action - San Martín, M. (1953)
The inhibition of the ovarian response with repeated gonadotropin, obtained from pregnant mare serum and urine of pregnant women use, has been described by several authors. Among the possibilities put forward to explain this antigonadotropic mentioned action of a mechanical obstacle in the ovarian surface; the ovarian exhaustion; The inhibitory action of the presence of active exert lutea; antihormone the one according to the system proposed by Collip; and finally, the possibility of an antigen antibody reaction